Validity of the auditory continuous performance test in differentiating central processing auditory disorders with and without ADHD. - Riccio CA; Cohen MJ; Hynd GW; Keith RW (Journal of Learning Disabilities, 1996)
The use of continuous performance tasks has been examined as a potential measure for clinical/laboratory identification of Attention-deficit/hyperactivity disorder. The present study compared the performance of 30 children, 26 boys and 4 girls ranging in age from 9-0 to 12-11 [sic], with central auditory processing disorders (CAPD) who did not meet criteria for coexisting ADHD with the performance of children with CAPD coexisting with ADHD (CAPD/ADHD) on the Auditory Continuous Performance Test (ACPT). In interpreting the results, the variability as well as the actual counts for correct responses and total errors were considered. Results indicated limited potential for the use of the ACPT in the differential diagnosis of ADHD. Implications of the results as well as considerations for future research are discussed.